2022
DOI: 10.26803/ijlter.21.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of High School Learners' Continuous Use of Mobile Learning during the Covid-19 Pandemic

Abstract: Every child has a right to education and attending school is a must in South Africa. However, school attendance was severely disrupted by the Covid-19 pandemic outbreak. Regardless, the academic process has to continue, hence the use of mobile devices as pedagogical tools for learning. The aim of this study therefore is to explore the determinants of high school learners' continuous use of mobile learning in order that the academic project may continue. The study employed a survey design in which quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Several studies have supported the belief that EUS influences users' intention to use a particular technology [40][41][42][43]. Similarly, previous research has indicated that users find M-learning technology useful and productive if its use does not require much time and effort [44][45][46][47][48]. Hence, it can be argued that students are more likely to use M-learning services if they find that doing so is not complicated.…”
Section: Literature Review and Research Background 21 Related Work On...mentioning
confidence: 88%
See 2 more Smart Citations
“…Several studies have supported the belief that EUS influences users' intention to use a particular technology [40][41][42][43]. Similarly, previous research has indicated that users find M-learning technology useful and productive if its use does not require much time and effort [44][45][46][47][48]. Hence, it can be argued that students are more likely to use M-learning services if they find that doing so is not complicated.…”
Section: Literature Review and Research Background 21 Related Work On...mentioning
confidence: 88%
“…According to previous studies [40][41][42][43], the TAM model is one of the most suitable models to measure the acceptance of M-learning among users. This model comprises five main factors-namely, AU, intention to use (IU), attitude (AT), EUS, and PUS-according to Davis [44][45][46]. These factors are considered to be predictors of the acceptance and usage of M-learning, according to previous studies [46][47][48].…”
Section: Hypotheses Of the Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In today's scienceand technology-rich society, such literacy is important to being a smart consumer and thoughtful participant in democratic decision-making and making sense of the world more generally. Thus, STEM education prepares a scientific and technical workforce, where integration is becoming increasingly common in cutting-edge research and development and a scientifically and technologically literate and more informed society [16]. The STEM-PjBL learning process in guiding students consists of five steps, each step aims to achieve a specific process.…”
Section: Stem-pjblmentioning
confidence: 99%
“…Third, it can enhance a sense of cooperation and use learning outcomes for the future [29][30][31]. Finally, these applications let students use self-regulated learning and let teachers use personalized instruction [32]. Based on the above, the rapid transition to mobile learning has started.…”
Section: Introductionmentioning
confidence: 99%